PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN VIDEO ANIMASI TERHADAP PEMAHAMAN KONSEP IPAS PESERTA DIDIK KELAS IV DI SD NEGERI 9 AMPENAN - Rahmawati; Tahir, Muhammad; Sobri, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using animated video learning media on the understanding of IPAS concepts among fourth-grade students at SD Negeri 9 Ampenan. This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The sampling technique used in this study was non-probability sampling, specifically purposive sampling.The data collection techniques used were tests and observation. The hypothesis was tested using an independent sample t-test. The results of the independent sample t-test showed that t_count > t_table, namely 2.953 > 2.014 and the sig. (2-tailed) value was < 0.05, namely 0.005 < 0.05, which means that Ha was accepted and Ho was rejected.Based on the results of the study, it can be concluded that the use of animated video learning media has an effect on the understanding of IPAS concepts among fourth-grade students at SD Negeri 9 Ampenan.